2019
DOI: 10.1128/jvi.02045-18
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Porcine Dermatitis and Nephropathy Syndrome in Piglets by Infection with Porcine Circovirus Type 3

Abstract: Porcine circovirus type 3 (PCV3) is an emerging porcine circovirus that has been associated with porcine dermatitis and nephropathy syndrome (PDNS)-like clinical signs, reproductive failure, cardiac pathologies, and multisystemic inflammation in piglets and sows. Many aspects of PCV3 infection biology and pathogenesis, however, remain unknown. Here, we used a PCV3 virus stock from the rescue of an infectious PCV3 DNA clone to intranasally inoculate 4- and 8-week-old specific-pathogen-free piglets for evaluatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
156
1
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(192 citation statements)
references
References 52 publications
9
156
1
2
Order By: Relevance
“…T. Thaiwong hypothesizes that CPV-2 infection predisposed dogs to CaCV-1 infection and ultimately resulted in more severe diseases (Thaiwong et al, 2016). Multiple studies indicated that PCV3 is associated with multiple diseases in infected pigs (Jiang et al, 2019). Similar to PCV2, PCV3 also co-infects with other swine pathogens (such as PCV2, classical swine fever virus, PRRSV) Zheng et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…T. Thaiwong hypothesizes that CPV-2 infection predisposed dogs to CaCV-1 infection and ultimately resulted in more severe diseases (Thaiwong et al, 2016). Multiple studies indicated that PCV3 is associated with multiple diseases in infected pigs (Jiang et al, 2019). Similar to PCV2, PCV3 also co-infects with other swine pathogens (such as PCV2, classical swine fever virus, PRRSV) Zheng et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Retrospective survey studies indicated that PCV3 infection could be traced back to 1996 . Recent studies confirmed that a PDNS-like disease is reproduced with PCV3 infection alone, and further research suggested that PCV3 is more pathogenic for piglets than PCV2 (Jiang et al, 2019).…”
Section: Introductionmentioning
confidence: 88%
“…PCV3 is associated with porcine dermatitis and nephropathy syndrome, congenital tremors, reproductive failure, and multi-systemic inflammation. PCV3 infection in piglets triggers inflammatory lesions in various tissues and organs followed by lymphocytic dysplasia and necrosis, and disruption of the immune system [20]. However, the exact pathogenesis of PCV3 remains unclear [21][22][23].…”
Section: Discussionmentioning
confidence: 99%
“…In 2016, the third PCV, named PCV3, was discovered using high-throughput sequencing technology in U.S. swine herds suffering from porcine dermatitis and nephropathy syndrome (PDNS), reproductive failure and other syndromes (11,12). A recent study suggested that PCV3 fulfilled Koch's postulates and could cause PDNS in piglets (13).…”
Section: Introductionmentioning
confidence: 99%